Sex differences and estrogen effects in cardiac mitochondria in human aortic stenosis and in the mouse heart - Fliegner, Daniela; Ellieva, Alexandra; Angelov, Anja; Petrov, Georgi; Regitz-Zagrosek, Vera (Frontiers in Endocrinology, 2023)
Introduction Sex differences in the adaptation to pressure overload have been described in humans, as well as animal models, and have been related to sex-specific expression of mitochondrial genes. We therefore tested whether sex differences in cardiac mitochondrial respiration exist in humans with aortic stenosis (AS). We also examined whether these potential differences may be at least partially due to sex hormones by testing if mitochondrial respiration is affected by estrogen (17ß-estradiol (E2)). Methods Consecutive patients undergoing transapical aortic valve implantation (TAVI) (women, n = 7; men, n = 10) were included. Cardiac biopsies were obtained during TAVI and used directly for mitochondrial function measurements. Male and female C57BL/6J mice (n = 8/group) underwent sham surgery or gonadectomy (GDX) at the age of 2 months. After 14 days, mice were treated once with intraperitoneally injected vehicle (placebo), 17ß-estradiol (E2), estrogen receptor alpha (ERα) agonist [propyl pyrazole triol (PPT)], or ER beta (ERβ) agonist (BAY-1214257). Thereafter, mitochondrial measurements were performed directly in cardiac skinned fibers from isolated left ventricles and musculus solei. Results Mitochondrial State-3 respiration was higher in female than that in male human heart biopsies (15.0 ± 2.30 vs. 10.3 ± 2.05 nmol/mL/min/mg, p< 0.05). In the mouse model, mitochondrial State-3 respiration decreased significantly after GDX in female (27.6 ± 1.55 vs. 21.4 ± 1.71 nmol/mL/min/mg; p< 0.05) and male hearts (30.7 ± 1,48 vs. 23.7 ± 2,23 nmol/mL/min/mg; p< 0.05). In ovariectomized female mice, E2 and ERβ-agonist treatment restored the State-3 respiration to intact placebo level, whereas ERα-agonist treatment did not modulate State-3 respiration. The treatment with E2, ERα-, or ERβ-agonist did not modulate the State-3 respiration in GDX male mice. Conclusion We identified sex differences in mitochondrial respiration in the diseased human heart. This is in alignment with known sex differences in the gene expression and proteome level at the functional level. E2 and ERβ affect cardiac mitochondrial function in the mouse model, suggesting that they may also contribute to the sex differences in the human heart. Their roles should be further investigated.